Association between olanzapine treatment and brain cortical thickness and gray/white matter contrast is moderated by cholesterol in psychotic disorders. (30th December 2018) - Gjerde, Priyanthi B.; Jørgensen, Kjetil N.; Steen, Nils E.; Melle, Ingrid; Andreassen, Ole A.; Steen, Vidar M.; Agartz, Ingrid
Highlights: The gray/white matter intensity contrast in olanzapine-treated psychotic patients is similar to healthy controls. Olanzapine-treated patients have thinner cortices compared to healthy controls. A higher serum HDL level during olanzapine treatment is related to thicker cortices. Our findings may represent a drug-related HDL effect on brain myelination. Abstract: Altered cortical brain morphology is observed in psychotic disorders. Despite the importance of lipid homeostasis for healthy brain functioning, knowledge about its role in cortical alterations in psychosis is limited. In a sample of patients with psychotic disorders, we investigated the relationship between treatment with olanzapine (OLZ), and cortical thickness and gray/white matter intensity contrast, and the association between these measures and serum lipid levels. We included 33 OLZ users, 19 unmedicated psychotic patients and 76 healthy controls (HC). Data on serum lipids and cortical measures based on MR brain images processed with FreeSurfer were analyzed with General Linear Models. We found that intensity contrast was similar in OLZ users as compared to HC and that the cortex (frontal, orbitofrontal, medial temporal) was thinner in OLZ users ( p < 0.05, Bonferroni corrected). An OLZ-specific HDL interaction effect was further found for the pericentral cortical thickness measure ( p < 0.05, Bonferroni corrected). Additionally, nominally significant findings indicated similar OLZ-specific interaction effects for cortical thickness in several regions, and an OLZ-specific interaction with LDL for occipital lobe contrast ( p < 0.05, uncorrected). Our findings may suggest a drug-related lipid-effect on brain myelination. Experimental studies and replications in different study samples are needed to clarify these complex relationships further.